Characterization of ferritin-bound anticancer drug - Beri, Nandita. (2013)
Magnetic resonance imaging (MRI) is a powerful diagnostic tool, which owing to its lack of unfavorable side effects has numerous applications in the biomedical field. However, limited sensitivity of currently available MRI contrast agents limits its application not only in molecular imaging but also in imaging of small tissue lesions. Magnetic nanoparticles are attracting attention as potential contrast agents for MRI, since their relaxivities are much higher than those of “classic” Gd(III) complexes. These relaxivities are further enhanced when nanoparticles are loaded into the cavity of an iron storage protein, ferritin. In the past, unique self-assembly properties of Archaeoglobus fulgidus ferritin (AfFtn) have been exploited as a template for such nanoparticles synthesis.